KELAYAKAN USAHA GULA AREN DI KAWASAN PENDUKUNG KOTAMOBAGU - Stivani Rompas; Esry H. Laoh; Gene Kapantouw (Universitas Sam Ratulangi, 2016)
ABSTRACTThis study aims to determine the feasibility of palm sugar in Poopo rural districts east passi. This study was conducted over six months from December until may 2016. This study uses census the number of entrepreneurs in the village Poopo palm suger is 7 and deliberatel chosen as respondents. The date used in the study are primary data and secondary, data primary data obtained through direct observation spaciousness and conduct interviews with farmers using a list of guestions (guestionnaires) that had been prepared. Secondary data were obtained from the agencies involved in this study. Analysis of the data used in this research is descriptive analysis.The result of this research showed that if the raw material of sugar palms not taken into account in cost of production and operating income sugar palms in the village poopo experienced a profit of 146.536/farmers and the day by R/C 2.55Key word : feasibility, business, supports, Kotamobagu